The flavonoid 7,8-DHF fosters prenatal brain proliferation potency in a mouse model of Down syndrome - Fiorenza Stagni (Nature Portfolio, 2021)
Abstract Neurogenesis impairment is a key determinant of intellectual disability in Down syndrome (DS), a genetic pathology due to triplication of chromosome 21. Since neurogenesis ceases after birth, apart in the hippocampus and olfactory bulb, the only means to tackle the problem of neurogenesis impairment in DS at its root is to intervene during gestation. A few studies in DS mouse models show that this is possible, although the drugs used may raise caveats in terms of safety. We previously found that neonatal treatment with 7,8-dihydroxyflavone (7,8-DHF), a flavonoid present in plants, restores hippocampal neurogenesis in the Ts65Dn model of DS. The goal of the current study was to establish whether prenatal treatment with 7,8-DHF improves/restores overall brain proliferation potency. Pregnant Ts65Dn females received 7,8-DHF from embryonic day 10 until delivery. On postnatal day 2 (P2) the pups were injected with BrdU and were killed after either 2 h or 52–60 days (P52–60). Evaluation of the number of proliferating (BrdU+) cells in various forebrain neurogenic niches of P2 mice showed that in treated Ts65Dn mice proliferation potency was improved or even restored in most of the examined regions, including the hippocampus. Quantification of the surviving BrdU+ cells in the dentate gyrus of P52–60 mice showed no difference between treated and untreated Ts65Dn mice. At P52–60, however, treated Ts65Dn mice exhibited a larger number of granule cells in comparison with their untreated counterparts, although their number did not reach that of euploid mice. Results show that 7,8-DHF has a widespread impact on prenatal proliferation potency in Ts65Dn mice and exerts mild long-term effects. It remains to be established whether treatment extending into the neonatal period can lead to an improvement in brain development that is retained in adulthood.